ADAM17, A Key Player of Cardiac Inflammation and Fibrosis in Heart Failure Development During Chronic Catecholamine Stress - Adu-Amankwaah, Joseph; Adzika, Gabriel Komla; Adekunle, Adebayo Oluwafemi; Ndzie Noah, Marie Louise; Mprah, Richard; Bushi, Aisha; Akhter, Nazma; Huang, Fei; Xu, Yaxin; Adzraku, Seyram Yao; Nadeem, Iqra; Sun, Hong (Frontiers in Cell and Developmental Biology, 2021)
Heart failure development is characterized by persistent inflammation and progressive fibrosis owing to chronic catecholamine stress. In a chronic stress state, elevated catecholamines result in overstimulation of beta-adrenergic receptors (βARs), specifically β2-AR coupling with Gαi protein. Gαi signaling increases the activation of receptor-stimulated p38 mitogen-activated-protein-kinases (p38 MAPKs) and extracellular signal-regulated kinases (ERKs). Phosphorylation by these kinases is a common way to positively regulate the catalytic activity of A Disintegrin and Metalloprotease 17 (ADAM17), a metalloprotease that has grown much attention in recent years and has emerged as a chief regulatory hub in inflammation, fibrosis, and immunity due to its vital proteolytic activity. ADAM17 cleaves and activates pro-inflammatory cytokines and fibrotic factors that enhance cardiac dysfunction via inflammation and fibrosis. However, there is limited information on the cardiovascular aspect of ADAM17, especially in heart failure. Hence, this concise review provides a comprehensive insight into the structure of ADAM17, how it is activated and regulated during chronic catecholamine stress in heart failure development. This review highlights the inflammatory and fibrotic roles of ADAM17’s substrates; Tumor Necrosis Factor α (TNFα), soluble interleukin-6 receptor (sIL-6R), and amphiregulin (AREG). Finally, how ADAM17-induced chronic inflammation and progressive fibrosis aggravates cardiac dysfunction is discussed.